Mediated climate rift society: articulation and metabolic rift theories in analyzing climate change news in South Africa - Evans, Henri-Count; Teer-Tomaselli, Ruth (Frontiers in Communication, 2023)
Introduction Journalism is essential in addressing climate change. Journalists' constructions of climate change issues, worldviews, and proposed solutions legitimise those aspects that are made commonsensical and are given discursive salience. The news media has often constructed climate change as a purely scientific issue whose solutions rely on technological interventions- thus neglecting climate change's cultural and political economics. This paper seeks to situate climate change journalism research within ecoCultural Studies and Environmental Sociology. Methods Through articulation and metabolic rift theories combined with discourse analysis techniques, this study examines how four weekly newspapers (the Sunday Times, the Mail & Guardian, the City Press, and the Sunday Independent) in South Africa reproduced and re/presented neoliberal climate change solutions anchored on “green” and “clean” transition discourses - from 2011 to 2018. Results The majority of discourse actors support the green economy initiative, with its normalisation facilitated by actors like scientists, media, and politicians. This discourse, prominent during both Zuma and Ramaphosa's administrations, has been integrated into South Africa's energy blueprints, emphasising job creation and cleaner air. While perpetuating capitalist inequalities, the green economy has been championed as a national project aligning with public aspirations. News media often portrays climate change solutions through a neoliberal, techno-optimistic lens, emphasising “green economy” and “sustainable development”. These solutions, paired with market principles, balance economic growth and environmental responsibility.